An Analytical Approach to Culture. Issue 4 (July 2023) - Lizardo, Omar
In this paper, I outline a general framework for cultural analysis consistent with an "analytic" approach to explanation in social science. The proposed approach provides coherent solutions to thorny problems in cultural theory. These include providing a coherent definition of culture (and the "cultural"), specifying the nature of cultural units (both simple and complex), and outlining the processes making possible episodes of cultural genesis, transformation, and reproduction within bounded units characterized as cultural causal systems.